Crossmodal attention applied lessons for and from driving - Spence, Charles 1969-; Soto-Faraco, Salvador 1970- (Cambridge University Press, 2020)
Cognitive neuroscientists have started to uncover the neural substrates, systems, and mechanisms enabling us to prioritize the processing of certain sensory information over other, currently less-relevant, inputs. However, there is still a large gap between the knowledge generated in the laboratory and its application to real-life problems of attention as when, for example, interface operators are multi-tasking. In this Element, laboratory studies on crossmodal attention (both behavioural/psychophysical and cognitive neuroscience) are situated within the applied context of driving. We contrast the often idiosyncratic conditions favoured by much of the laboratory research, typically using a few popular paradigms involving simplified experimental conditions, with the noisy, multisensory, real-world environments filled with complex, intrinsically-meaningful stimuli. By drawing attention to the differences between basic and applied studies in the context of driving, we highlight a number of important issues and neglected areas of research as far as the study of crossmodal attention is concerned
Title from publisher's bibliographic system (viewed on 14 Aug 2020)
Keywords: Attention; Cognitive neuroscience; Distracted driving